Does Glossing Affect Thai EFL Students’ Reading Comprehension and Lexis Acquisition? - Jenpattarakul, Win (Mediterranean Journal of Social Sciences, 2012)
This study was a one-group pretest-posttest experiment and aimed to investigate the effect of glossing on readingcomprehension and lexis acquisition of 30 Bangkok University students and explores their attitude towards the use of glossing.The instruments were the reading comprehension tests, and the questionnaire exploring attitude towards glossing. The pretestand posttest scores of the experimental group were calculated by descriptive statistics and compared by using a dependent t-Test measure. It was found that students obtained higher scores for the posttest than the pretest scores at the 0.05 level ofsignificance. In addition, their attitude towards using glossing was at a high level. Moreover, the results from this study supportedthat using glossing helped the students remember vocabulary and can be a substitute for a dictionary consultation whenencountering low frequency words in a reading passage. Pedagogical implications into reading comprehension and lexisacquisition were suggested.